2018
DOI: 10.1021/acsenergylett.8b02207
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Phase Segregation in Mixed Halide Perovskites through Nanocrystal Size

Abstract: Mixed halide perovskites are one of the promising candidates in developing solar cells and light-emitting diodes (LEDs), among other applications, because of their tunable optical properties. Nonetheless, photoinduced phase segregation, by formation of segregated Br-rich and I-rich domains, limits the overall applicability. We tracked the phase segregation with increasing crystalline size of CsPbBr3–xIx and their photoluminescence under continuous-wave laser irradiation (405 nm, 10 mW cm–2) and observed the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
183
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(204 citation statements)
references
References 43 publications
12
183
1
Order By: Relevance
“…Gualdrón-Reyes and colleagues [59] corroborate these results. In their study, (x = 0.11, 0.52, and 0.79) CsPb(I 1-x Br x ) 3 films with average grain sizes below~45 nm exhibit suppressed halide segregation under CW illumination (λ exc = 405 nm; I exc = 10 mW cm -2 ).…”
Section: Models For Light-induced Halide Segregationmentioning
confidence: 62%
“…Gualdrón-Reyes and colleagues [59] corroborate these results. In their study, (x = 0.11, 0.52, and 0.79) CsPb(I 1-x Br x ) 3 films with average grain sizes below~45 nm exhibit suppressed halide segregation under CW illumination (λ exc = 405 nm; I exc = 10 mW cm -2 ).…”
Section: Models For Light-induced Halide Segregationmentioning
confidence: 62%
“…† In Fig. S3a † the increase in V oc as a function of bromide content is related with the change in the bandgap, [16][17][18]36,49 as shown in Fig. S4 and Table S1.…”
Section: Resultsmentioning
confidence: 95%
“…47 It has also been reported that as the amount of bromide is increased, phase segregation can occur, particularly when the lm is under illumination. 16,40,41 Phase separation causes the 28.8 peak to split into two peaks, associated with iodide and bromide rich regions. 40,41 No phase separation was observed in these samples, although these lms were not exposed to light before the XRD spectrum was measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the (100)/(111) Cu 2 O was characterized by Kelvin probe force microscopy (KPFM) at ambient condition to determine the surface potential on the exposed (100) and (111) planes. For a semiconductor, the surface potential is always related to the surface energy of a material, which differs from the bulk work function ascribed to the formed space charge region near the interface . Therefore, surface potential mainly reflects the properties of a thin surface layer, such as surface work function and Fermi level.…”
mentioning
confidence: 99%